Charlie Wilson's war - Crile, George; Goetzman, Gary; Hanks, Tom; Hoffman, Philip Seymour, 1967-; Nichols, Mike; Roberts, Julia, 1967-; Sorkin, Aaron; Participant Productions; Playtone (Firma); Relativity Media; Universal Pictures (Firma) (United States : Universal Pictures, 2007)
Un drama sobre la base de un congresista de Texas Charlie Wilson de relaciones encubiertas en Afganistán, donde sus esfuerzos para ayudar a los rebeldes en su guerra con los soviéticos tienen algunos imprevistos y largo alcance.
Basado en el libro por George Crile.
Copyright Claimant: Universal City Studios Productions LLLP. MP Munich Pape Filmproductions GmbH & Co. KG. PREV: Previously published music used with permission; based on book by George Crile. Basis of Claim: All other cinematographic material. Date of Creation: 2007; Date of Publication: December 14, 2007; Registration Number / Date: PA0001591563 / 2008-01-22.
DISPONIBLE
Not viewed.
Sources used: copyright database; Variety Web site, review posted Nov. 28, 2007, viewed Mar. 18, 2008; Internet movie database, viewed Mar. 18, 2008; FirstSearch, OCLC 191886923, viewed Mar. 18, 2008.
Summary from FirstSearch, OCLC 191886923, viewed Mar. 18, 2008.
Keywords: Wilson, Charles, -- 1933- -- Drama; United States. -- Inteligencia militar -- Drama; Asistencia militar -- Afganistán -- Drama; Afganistán -- Historia -- Ocupación soviética, 1979- -- Drama; Adaptación -- Largometraje para televisión; Biográfico -- Largometraje para televisión